Pengaruh Kepuasan Kerja, Lingkungan Kerja, dan Beban Kerja Terhadap Kinerja Karyawan PT Finansial Integrasi Teknologi - Agus Setiawan,; Mochamad Rizki Sadikin, (Jurnal Publikasi Ilmu Manajemen, 2025)
This research was conducted with the aim of analyzing the influence of job satisfaction, work environment and workload on employee performance of PT employees. Financial Integration Technology. A total of 104 PT employees. Financial Technology Integration respondents in this research used a saturated sample method. This research uses structural equation modeling (SEM) data analysis techniques and data processing using Partial Least Square (PLS). The results of this research show that work discipline, work environment, and job satisfaction have a positive and significant effect on employee performance at PT employees. Financial Integration Technology. The results of the managerial mandate from the findings in this research recommend that leaders be more stringent in supervising employees, apart from that PT. Financial Technology Integration is also recommended to maintain cleanliness around the environment where employees work, and finally PT. Financial Technology Integration is also expected to provide more sufficient time for employees to complete work.